Utilization of Government Livestock Grant Funds Among Goat Farmers - Ismiaji, Bara; Azizah, Siti; Rachmawati, Achadiah; Nurzaman, Syaifulloh Ibnu Alam (PT. Riset Press International, 2025)
The livestock grant program initiated by the Kediri Regency Government aimed to improve livestock numbers and productivity. However, since the funds were first distributed in 2022, the goat population in Puncu Sub-district has shown fluctuating trends, while Kepung Sub- district has experienced a consistent increase. This study seeks to investigate the utilization of grant funds by the farmer groups using case study with explorative approach. Most groups utilized the funds primarily for goat procurement, with a focus on breeding activities, employing farming practices that ranged from traditional to semi-intensive systems. Jawarandu and Peranakan Etawa (PE) were the most preferred goat breeds among the farmer groups. The farming approaches varied across groups, including collective, semi-collective, and individual management, reflecting differences in available resources, organizational maturity, and group objectives. Despite these variations, the majority of groups followed technical guidelines and used the grant funds as initial capital to start or improve their goat farming activities. Key factors supporting effective fund utilization included access to local feed resources, flexible fund usage guidelines, veterinary support, strong member solidarity, and accessible goat marketing channels. On the other hand, challenges included seasonal feed shortages, limited health and reproductive management practices, and difficulties in monitoring goats when housed individually. These findings provide valuable insights for policymakers in designing more responsive and sustainable livestock grant programs and may serve as a basis for future research on the programs impacts.